Pengembangan E-Learning Berbasis LMS Computational Thinking Platform Flipped Classroom di SMA Negeri 18 Luwu Utara - Haryanti Haryanti; Firdaus Daud; Muhammad Danial (UNM Journal of Biological Education, 2023)
This research aims to produce LMS-based Biology   e-learning media at SMA Negeri 18 Luwu Utara that is valid, practical and effective, as well as analyze the practicality and effectiveness of the developed e-learning media  .  The research method used is Research & Development (R&D mode used is the Development Model of Robert Maribe Branch (2009) with 5 stages in a cycle, namely ADDIE (Analysis, Design, Development, Evaluation). Sampling uses a simple random sampling technique. The sample of this study is class XII MIPA1 which amounts to 34 students. Kevalidan, Practicality is collected with questionnaire and validation sheets, for effectiveness data is collected with test sheets. Data collection is carried out by testing the validity of products, providing learning outcome tests, collecting student and teacher response data. The data collected was analyzed using quantitative descriptive analysis with the results: 1) The validity of media experts and materials received valid categories from 2 validators; 2) Classical completion of learning outcomes of 88.23%;  3) Teachers and students respond positively to the product, 4) there is a significant link between practicality and effectiveness of the media. Based on the results of the study, the e-learning media  developed is declared valid, practical and effective.